Golda Meir A Political Biography - Medzini, Meron (De Gruyter Oldenbourg, 2017)
For five decades Golda Meir was at the center of the political arena in Israel and left her mark on the development of the Yishuv and the state. She was a unique woman, great leader, with a magnetic personality, a highly complex individual. She held some of the most important positions that her party and the State could bestow. She fulfilled most of them with talent and dignity. She failed in the top job - that of Prime Minister. This biography traces her origins, her American roots, her immediate family, her failed marriage, her rise in the party, the trade union movement, her massive and enduring achievements as Secretary of Labor and Housing, her ten year stint as foreign minister and finally the reasons that led to her failure as prime minister. She was a very good tactician, far less a strategist. She was a major builder of modern Israel whose influence on that country, on Israel-American relations and on Jewish history was evident primarily from 1969 to 1974.